KOMPETENSI PEDAGOGIK GURU AGAMA KATOLIK SEKOLAH DASAR DI KABUPATEN BANTUL - I Wayan Setioka; Pardjono Pardjono (Faculty of Education, Universitas Negeri Yogyakarta, 2016)
Penelitian ini bertujuan mengungkap: (1) kompetensi pedagogik guru agama katolik SD di Kabupaten Bantul, (2) mengetahui bagaimana kaitan latar belakang profil guru dengan kompetensi pedagogik guru agama katolik SD di Kabupaten Bantul. Penelitian ini menggunakan pendekatan kuantitatif jenis deskriptif. Penelitian ini dilakukan pada bulan November dan Desember 2013. Data dikumpulkan melalui angket isian pertanyaan dan tes. Populasi penelitian ini adalah 28 orang guru agama Katolik Sekolah Dasar di Kabupaten Bantul. Hasil analisis deskriptif menunjukkan bahwa: (1) kompetensi pedagogik guru agama katolik Sekolah Dasar di Bantul dalam kategori cukup; (2) latar belakang pendidikan belum berkontribusi meningkatkan kompetensi pedagogik guru; (3) latar belakang masa kerja menjadi guru belum berkontribusi meningkatkan kompetensi pedagogik guru; (4) tingginya pangkat golongan ruang belum berkontribusi meningkatkan kompetensi pedagogik guru agama katolik SD di Bantul; (5) latar belakang pendidikan, lamanya masa kerja, pangkat golongan ruang guru, belum berkontribusi meningkatkan kompetensi pedagogik guru agama katolik SD di Kabupaten Bantul. Kata Kunci: Kompetensi pedagogik, latar belakang guru THE PEDAGOGIC COMPETENCY OF CHATOLIC RELIGION ON ELEMENTARY SCHOOL OF BANTUL REGENCY Abstract This research is aimed to: (1) reveal the pedagogic competency of chatolic religion on elementary school of Bantul regency, (2) know the relationship between the profile background of teacher with the the pedagogic competency of chatolic religion on elementary school of Bantul regency. This reasearch was carried out on November and December 2013. The collecting data technique used is questionnaire and test. It is a research of quantitative descriptive. The population of the research is all teachers of chatolic religion on elementary school in Bantul regency. There are 28 teachers of chatolic religion on elementary school in Bantul regency. The descriptive analysis shows that: (1) the pedagogic competency of chatolic religion on elementary school of Bantul regency is in the category adequate or satisfactory; (2) the education background does not automatically enhance pedagogic competency, (3) the background of long working period does not automatically contribute to the pedagogic competency; (4) the level of position does not automatically contribute to the pedagogic competency of catholic teachers of elementary school in Bantul regency, (5) the education background, the working period, the working position rank do not automatically enhance the pedagogic competency of catholic teachers in Bantul regency. Keywords: pedagogic competency, the teacher background